ANALISA KADAR TIMBAL (Pb) PADA GORENGAN YANG DISAJIKAN MENGGUNAKAN PENUTUP DAN TIDAK MENGGUNAKAN PENUTUP PADA KAWASAN TRAFFIC LIGHT KOTA MEDAN TAHUN 2012 - Ardalina .; wirsal hasan; Indra Chahaya (Lingkungan dan Kesehatan Kerja, 2013)
Analysis of lead (pb) in snack foods served using a cover and without cover a round traffic light in the city of Medan in 2012. Snack foods such as fried bananas favored by many people. Food-borne illness cause of foods served does not eligible hygiene and food sanitation. Fried presented a round the traffic light is not served by closed container. The cover is estimated to effect pollution of lead (Pb) in the food. This study aimed to determine levels of lead (Pb) in the snack foods served using a cover and without it a round traffic light in the city of Medan in 2012. This study was descriptive research, to know the levels of lead (Pb) in the snack foods served using a cover and without it a round traffic light in the city of Medan in 2012. Results of this research showed there was all samples contained lead (Pb). Object of this research is 10 samples of fried bananas, consist of 5 samples were using a glass cover and 5 samples were without it. Highest levels of lead (Pb) is in fried foods served a round the traffic light of Pinang Baris, which is 2.89 ppm. Lowest levels of lead (Pb) is in fried foods served a round the traffic light of Komplek Tasbi, which is 2.04 ppm. Snack foods served using a cover was qualify by set under Threshold Limit Value and all levels of lead (Pb) in the fried banana without a cover a round the traffic light was unqualify by set under Regulation of BPOM RI No. 03725/B/SK/VII/89 a bout maximum limit of metal pollution in food. Contamination of lead (Pb) has occurred in snacks food served using a cover and without it a round traffic light in the city of Medan in 2012. Cover reduces the pollution of lead (Pb) in snack foods. Therefore, a cover should be used to snack foods when serving it a round the traffic light. Keywords : Lead (Pb), Snack Foods, Cover, Without Cover, Traffic Light